Protocol-based anticoagulation management for mechanical circulatory support patients can be safe and efficient. Issue 6 (June 2022) - Birk, Sarah E; Ingemi, Amanda; Bourassa, Patricia; Neumann, Karl; Pine, Carly; Seigh, Mindy; Cassa, Hannah; Sullivan, Margaret; Baran, David A; Herre, John M; Yehya, Amin
Background: Achieving optimal anticoagulation remains a significant challenge in managing patients on left ventricular assist device (LVAD) support. Maintaining tight control of anticoagulation can be time-consuming but essential in preventing serious complications such as pump thrombosis and bleeding. Objectives: The efficacy and safety of a nurse coordinator-driven outpatient protocol (NCDOP) was evaluated for managing anticoagulation for LVAD patients. Methods: A retrospective analysis was performed as part of a single-center quality improvement project. The primary outcome was time in therapeutic range (TTR), a measure of anticoagulation target efficacy before and after the implementation of the protocol. Results: Among 47 patients, who served as their own control, there was no significant change in TTR or proportion of hospitalizations following institution of the protocol. Pre-NCDOP, there were six major bleeding and two thrombotic events, and none during the post-NCDOP period. Conclusions: A NCDOP is a reliable method to manage anticoagulation in LVAD patients and facilitates efficient care delivery. Future multicenter studies with larger patient cohorts are warranted to expand on the findings outlined in this manuscript.